2022
DOI: 10.3168/jds.2021-21274
|View full text |Cite
|
Sign up to set email alerts
|

Residual feed intake in peripartal dairy cows is associated with differences in milk fat yield, ruminal bacteria, biopolymer hydrolyzing enzymes, and circulating biomarkers of immunometabolism

Abstract: Residual feed intake (RFI) measures feed efficiency independent of milk production level, and is typically calculated using data past peak lactation. In the current study, we retrospectively classified multiparous Holstein cows (n = 320) from 5 of our published studies into most feed-efficient (M-eff) or least feed-efficient (L-eff) groups using performance data collected during the peripartal period. Objectives were to assess differences in profiles of plasma biomarkers of immunometabolism, relative abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Different from signi cantly abundant bacteria mainly distributed at the species level, the abundant bacteria in the swab samples were distributed at the multi-levels. The populations of Prevotella ruminicola increased with increasing guanidinoacetic acid (GAA) addition 21 , and were associated with feed e ciency 22 . Network showed that lots of speices(Prevotella brevis, Prevotella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Different from signi cantly abundant bacteria mainly distributed at the species level, the abundant bacteria in the swab samples were distributed at the multi-levels. The populations of Prevotella ruminicola increased with increasing guanidinoacetic acid (GAA) addition 21 , and were associated with feed e ciency 22 . Network showed that lots of speices(Prevotella brevis, Prevotella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella ruminicola under Bacteroidetes was abundant at every levels. The populations of Prevotella ruminicola increased with increasing guanidinoacetic acid (GAA) addition [50] were associated with feed e ciency [51].…”
Section: Discussionmentioning
confidence: 99%
“…Body condition score loss is often observed in transition dairy cows, mainly caused by a reduction in DMI ( Janovick and Drackley, 2010 ; Elolimy et al, 2022 ). This reduction in prepartum DMI and, consequently, alteration in prepartum BCS has been linked to impaired immunity ( Hammon et al, 2006 ); increased incidence of health disorders ( Huzzey et al, 2007 ); lower milk yield, quality, and composition; and poor reproductive performance ( Dennis et al, 2022 ).…”
mentioning
confidence: 99%